Restoration of degraded landscapes for ecosystem services in North-Western Ethiopia. Issue 8 (August 2018) - Mekuria, Wolde; Wondie, Menale; Amare, Tadele; Wubet, Asmare; Feyisa, Tesfaye; Yitaferu, Birru
Abstract: Establishing exclosures has become common in Ethiopia, especially in the central and northern highlands, where they serve as a response to persistent forest degradation, affecting forest resources and ecosystem services. We investigated changes in vegetation composition, aboveground biomass and soil properties after establishing an exclosure on degraded communal grazing land in Aba-Gerima watershed, North-Western Ethiopia. We selected 4-yr-old exclosure and paired the selected exclosure with an adjacent communal grazing land. In the exclosure, we recorded 46 plant species representing 32 families, whereas we recorded 18 plant species representing 13 families in the adjacent communal grazing lands. Most of the identified woody species are economically important. We observed significant differences between the exclosure and adjacent grazing land in woody species richness, diversity and evenness. Exclosure displayed higher woody species density, basal area and aboveground woody biomass compared to the adjacent grazing land. Landscape position influenced vegetation composition, richness and diversity in the exclosure and adjacent grazing land. Significant differences between the exclosure and adjacent grazing land in soil properties were detected. The influence of landscape positions on soil properties was not consistent. At foot slope position, in the 0- to 15-cm and 15- to 30-cm depths, soil organic carbon and nitrogen content detected in exclosure were significantly higher when compared to the values observed in the adjacent grazing land. However, differences at mid and upper slope positions were not significant. The results support that the establishment of exclosures on degraded lands could support the restoration of degraded native vegetation and soil properties, which consequently enhance the ecosystem services that can be obtained from degraded lands.